STRATEGI PENGELOLAAN DESA WISATA GIYANTI, KABUPATEN WONOSOBO - Dini Puspita; Susi Sulandari (Journal of Public Policy and Management Review, 2016)
Tourism sector is a sector which can increase revenue for the region. Wonosobo have a very diverse tourism potential. One of them is the Tourism Village Giyanti which is very famous for the traditional culture and dances. Giyanti village also served as a Tourism Village and being one of the tourism potential object in Wonosobo Regency. But it has not been managed well in Wonosobo Regency. The focus and goal of this study is to formulate strategy for the management of tourist villages. It used the method of SWOT analysis (Strength, Weakness, Opportunities, Threats) analysis of existing strategic environment in the management of the Tourism Village. This study used a qualitative descriptive type by using informants from the Giyanti Village, and the Office of Tourism and Creative Economy Wonosobo District, as well as the Central Java Provincial Tourism Office. The results of the study management in Giyanti Tourism Village haven’t not maximized yet. By analyzing the internal and external environment are obtained strategies then using Litmus test to measure the level of strategic issues based on the scores of existing programs. Based on these results, it is suggested that the strategic programs that have been formulated can be implemented and applied consistently in Tourism Village Giyanti. This is done in order to improve management of the Tourism Village Giyanti to a better direction.